2018
DOI: 10.1016/j.indcrop.2017.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of highly sustainable polylactide/almond shell flour composites by reactive extrusion with maleinized linseed oil

Abstract: Highly sustainable composites were produced by melt compounding polylactide (PLA) with almond shell flour (ASF), a processed byproduct of the food industry, at a weight content of 30 wt.-%. However, due to the lack of miscibility between PLA and ASF, both being raw materials obtained from crops, resultant green composite presented poor ductility and low thermal stability. To overcome this limitation, maleinized linseed oil (MLO), a multi-functionalized plant-derived additive, was originally incorporated as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
128
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 64 publications
(87 reference statements)
14
128
0
3
Order By: Relevance
“…Concerning the use of ESAO a 1wt% was added, the manufacturer recommends an amount between 0.1–1 wt% since higher loadings lead to undesired effects such as gel formation which, in turn, leads to a decrease in mechanical properties. This behaviour has also been reported by Torres‐Giner et al Finally, regarding MLO, it is a relatively new compatibilizer and previous results suggest 5 wt% offers comparable results to the other compatibilization systems …”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Concerning the use of ESAO a 1wt% was added, the manufacturer recommends an amount between 0.1–1 wt% since higher loadings lead to undesired effects such as gel formation which, in turn, leads to a decrease in mechanical properties. This behaviour has also been reported by Torres‐Giner et al Finally, regarding MLO, it is a relatively new compatibilizer and previous results suggest 5 wt% offers comparable results to the other compatibilization systems …”
Section: Methodssupporting
confidence: 85%
“…The tensile strength decreases from 62.5 MPa for PLA‐DE without any coupling agent/compatibilizer to 40 MPa for PLA‐DE‐MLO biocomposite. This is a direct consequence of the plasticization effect that MLO can provide . Accordingly, the elongation at break increases to 13.8%, which is almost three times the PLA‐DE value.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, the efficiency of vegetable oil-based plasticizers is very poor as, in general, a very slight decrease on the glass transition temperature is achieved. Nevertheless, the highly reactive groups in modified vegetable oils (mainly epoxy, acrylate, maleic anhydride groups, among others) can react with hydroxyl groups present in the end chains of polyesters thus leading to additional reactions that could lead to chain extension, branching and crosslinking simultaneously as reported by Quiles-Carrillo and coworkers [41][42][43] in several works. With regard to Joncryl ® , typical amounts of 1 wt% are recommended by suppliers to avoid gel formation by crosslinking.…”
Section: Disintegration In Controlled Compost Soilmentioning
confidence: 99%
“…So that, it is expectable a more intense overlapping of chain extension, branching and crosslinking when using ECSO and MCSO than in the case of Joncryl ® (Figure 3c). A FTIR study carried out by Quiles-Carrillo et al [43] on poly(lactic acid) with lignocellulosic fillers demonstrated the reaction between maleinized linseed oil (MLO) and hydroxyl groups in PLA end chains and cellulose particles therefore giving clear evidences of reactive extrusion.…”
Section: Disintegration In Controlled Compost Soilmentioning
confidence: 99%